Modernism and Cosmology - Ebury, K. author. aut Link
VII, 210 p.
Keywords: Through examining the work of W. B. Yeats, James Joyce, and Samuel Beckett, Katherine Ebury shows cosmology had a considerable impact on modernist creative strategies, developing alternative reading models of difficult texts such as Finnegans Wake and 'The Trilogy'.